Current classification of lung carcinoma. Histological, immunophenotypic, molecular and clinical considerations - Barrionuevo Cornejo, Carlos (2019)
In recent years, the rapid technological development and the better knowledge of genetic and molecular aspects in medicine have allowed a better approach to understand, diagnose and treat various oncological diseases. Regarding lung carcinoma, there has been a remarkable evolution from the first classifications, which were purely morphological, to the last one issued in 2015. This last classification includes histological, immunophenotypic, molecular genetics, clinical and radiological information, which allows a better evaluation and therapeutic management of these patients. In the present article, the first classifications of lung carcinoma to the last one are reviewed, and the most relevant changes and the importance of the molecular genetics findings are examined for a better clinical and therapeutic approach.